MARKET SHARE DETERMINAN OF ISLAMIC COMMERCIAL BANKS - Lia Safrina; Uswatun Hasanah; Hartanti Dewi; Vita Arum Sari (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2025)
The growth of the market share value of Islamic banks from 2018 to 2023 has fluctuated but tends to increase, even reaching a market share value of 7.44% in 2023. This achievement has not yet met the market share target set by Bank Indonesia since 2015, which is 15%. This research aims to analyze the influence of BOPO, NPF, and FDR on Share. This study uses secondary data obtained from the official website of the OJK and the official websites of each Islamic Commercial Bank in the form of quarterly financial statements from 2021 to 2023 from 11 Islamic commercial banks. The data analysis model used in this research is the Panel Data Regression model. The results of the simultaneous test show that the variables BOPO, NPF, and FDR have a positive and significant effect on market share. Partially, the BOPO and NPF variables do not have an effect on market share, while the FDR variable has a positive and significant effect on market share.